SUBSURFACE STRUCTURE ANALYSIS BASED ON MODELING RESULTS FROM MAGNETIC AND GRAVITY DATA IN MOUNT AGUNG AND MOUNT BATUR AREA, BALI. - Fajar Gumilang, Mukhamad
Indonesia is a region that has many volcanoes, this causes Indonesia to be included in the region's rings of fire. Active volcanoes on the island of Bali include Mount Agung and Mount Batur. The volcano has different volcanic products with varying physical properties of the rock. Magnetic and gravity methods are one of the methods in geophysics to model subsurface structures. The magnetic data used in this study were taken directly, and there is secondary data in the form of gravity data to strengthen the modeling results. Modeling is done with the help of Oasis Montaj software. In addition, the susceptibility and density data of the rocks in the study area are used in modeling the subsurface structure. In this study the susceptibility values used have a value range of 0.00001 – 0.035 m3/Kg, while the density value has a value range of 1.82 – 2.8 g/cm3. Modeling is done by making three tracks that pass through Mount Agung and Mount Batur. From the modeling that has been done, produce a subsurface structure that is in accordance with the geological conditions of the study area. There is a shallow magma chamber under Mount Agung and Mount Batur at a depth of 3-7 km. In addition, there is an intrusion between Mount Agung and Mount Batur which connects the two shallow magma chambers with deeper magma chambers.